Analisis Strategi Guru IPAS dalam Membangun Minat Siswa dengan Media Sederhana - Septiani Fatikhatus Sholihah; Novi Ismiasih (Fakultas Tarbiyah Institut Pesantren Sunan Drajat Lamongan, 2025)
This study aims to analyze the strategies used by IPAS teachers in fostering students’ interest through the use of simple media in the topic of light, particularly light refraction. The research was conducted at MI Mu’awanah in July 2025 using a qualitative approach with a descriptive method. Data were collected through interviews with an IPAS teacher, classroom learning observations, and documentation in the form of notes and pictures during the process. Data analysis was carried out by reducing, presenting, and drawing conclusions from the findings in the field. The results show that the IPAS teacher utilized simple media in the form of a glass of water with a pen inside it to explain the phenomenon of light refraction. This medium proved effective as it was able to capture students’ attention and helped them better understand the abstract concept by making it more concrete. Classroom observations revealed that students demonstrated high enthusiasm throughout the learning process. They actively observed the experiment, responded, and were able to answer the teacher’s questions well. Interviews with the teacher also reinforced the finding that using simple media can serve as a relevant and easily applicable strategy in IPAS learning both in elementary and secondary schools. Thus, it can be concluded that the strategy of using simple media plays an important role in fostering interest as well as enhancing students’ understanding of the concept of light refraction. This study emphasizes that simple media are not only affordable and easy to obtain but also capable of creating an interactive, engaging, and meaningful learning atmosphere for students